Comparative Study on Numerical Methods for Singularly Perturbed Advanced-Delay Differential Equations - P. Hammachukiattikul; E. Sekar; A. Tamilselvan; R. Vadivel; N. Gunasekaran; Praveen Agarwal (Journal of Mathematics)
In this paper, we consider a class of singularly perturbed advanced-delay differential equations of convection-diffusion type. We use finite and hybrid difference schemes to solve the problem on piecewise Shishkin mesh. We have established almost first- and second-order convergence with respect to finite difference and hybrid difference methods. An error estimate is derived with the discrete norm. In the end, numerical examples are given to show the advantages of the proposed results (Mathematics Subject Classification: 65L11, 65L12, and 65L20).